Role of total quality management on innovation performance: Moderating Effect of organizational learning - Abolfazl Kazzazi; Abbas shoul (مطالعات مدیریت بهبود و تحول, 2013)
This article investigates the impact of total quality management and organizational learning on innovation performance in MES company. A sample of 93 managers and experts in MES company, instrument for data collection was questionnaire.TQM is made up of top management support, employee involvement, continue improvement, and customer focus that customer focus and employee involvement have the highest and lowest factor loading. Also innovation performance made up of product innovation, process innovation, and organizational innovation. Process innovation and organizational innovational have the highest and lowest factor loading. Organizational learning is moderate variable that is made up of learning culture and learning strategy.The result of structural equation modeling showed that innovation performance is affected significantly by TQM (79%), and this effect is moderated by organizational learning